2021
DOI: 10.1038/s41467-021-21028-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM of mammalian PA28αβ-iCP immunoproteasome reveals a distinct mechanism of proteasome activation by PA28αβ

Abstract: The proteasome activator PA28αβ affects MHC class I antigen presentation by associating with immunoproteasome core particles (iCPs). However, due to the lack of a mammalian PA28αβ-iCP structure, how PA28αβ regulates proteasome remains elusive. Here we present the complete architectures of the mammalian PA28αβ-iCP immunoproteasome and free iCP at near atomic-resolution by cryo-EM, and determine the spatial arrangement between PA28αβ and iCP through XL-MS. Our structures reveal a slight leaning of PA28αβ towards… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 88 publications
0
28
0
Order By: Relevance
“…Furthermore, binding of PA28αβ or PA28γ induces conformational changes in the β-rings, the proteasomal active sites, and therefore might modify the 20S products. In addition, the cryo-EM structure of mammalian PA28αβ-immunoproteasome 20S complex suggests that this complex has experienced profound remodelling during evolution to achieve its current level of function in immune response [110]. These data indicate that the binding of regulators to the 20S proteasome allosterically modifies 20S proteasome activity.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, binding of PA28αβ or PA28γ induces conformational changes in the β-rings, the proteasomal active sites, and therefore might modify the 20S products. In addition, the cryo-EM structure of mammalian PA28αβ-immunoproteasome 20S complex suggests that this complex has experienced profound remodelling during evolution to achieve its current level of function in immune response [110]. These data indicate that the binding of regulators to the 20S proteasome allosterically modifies 20S proteasome activity.…”
Section: Discussionmentioning
confidence: 95%
“…The protein complex for this previous study was produced by heterologous coexpression of the two subunits, which form a 4α/3β assembly reportedly due to a more thermodynamically stable α-α interface compared to the β-β interface. A more recent cryo-EM study of heterologously expressed human PA28 mixed in vitro with bovine 20S also made a similar conclusion 9 . Interestingly, our study of the endogenous human PA28-20S proteasome revealed a different stoichiometry of PA28.…”
Section: Stoichiometry Of the Endogenous Pa28mentioning
confidence: 60%
“…The other six unique binding pockets are well engaged with the corresponding C termini of the PA28 3α/4β assembly. On the other hand, the PA28 4α/3β assembly derived from heterologous coexpression showed only partial association with native 20S when assembled in vitro 9 . These results suggest that PA28 in a 4α/3β arrangement has reduced binding affinity to 20S compared to a 3α/4β shows PA28 associating tightly with 20S, resulting in well-defined density for the entire complex.…”
Section: Stoichiometry Of the Endogenous Pa28mentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, in this case PA28 was found to bind 20S asymmetrically, strongly engaging subunits on only one side of the core particle [9]. However, strong evidence indicating that PA28 may also act through long distance allosteric modifications of proteasomal proteolytic sites has been recently reported [10][11][12].…”
Section: Introductionmentioning
confidence: 91%